La pérdida violenta: duelo prolongado y estrés postraumático en adultos: revisión aplicada - Adrianzen Sandoval, Joan Manuel (2023)
A violent death is characterized by being unexpected and heartbreaking, especially when it involves significant others. The literature shows that this experience could lead to the development of Posttraumatic Stress Disorder (PTSD) as well as Prolonged Grief Disorder (PGD). In this applied review, the association between these disorders in adults who lost someone close to them due to violent death was studied through the analysis of ten scientific articles from the following databases: Proquest, APA PsycNET, Ebsco and Scopus. The PRISMA guidelines were taken into account in such research (Page et al., 2021). Thus, large, positive and statistically significant correlation between the constructs was found, with little to no impact of variables such as type of death, number of deceased significant others, age or time since death. Despite being a population highly exposed to violent death due to its socio-political context, only one article was found in Latin America. All in all, it is recommended to increase the research about the comorbidity between PTSD and PGD for this population and, later on, to develop a validated intervention protocol.